“The Location of Technological Innovations within the Japanese Semiconductor Industry” - Tomokazu Arita; Philip McCann (European Regional Science Association (ERSA), 2001)
Much of the current literature on hi-tech developments within the electronics industry tends to focus on the spatial and organisational arrangements evident in innovative clusters such as Silicon Valley. There are, however, many very different forms of spatial organisation which engender innovations within the semiconductor industry and these variations depend on the particular sub-sector of the semiconductor industry. In this paper we discuss the case of Japanese vertically integrated semiconductor producers. The paper will analyse data from over 200 Japanese semiconductor firms located in Japan. In particular, we will focus on the firms undertaking the wafer manufacturing processes. We develop a series of regressions which relate the various measures of production technology and innovation to firm plant and location characteristics at a prefecture level. Our results indicate that the spatial arrangements here are very different from those evident in the US or Europe.
Keywords: 330